ASEAN & HUMAN RIGHTS REGIME: BIBLIOMETRIC ANALYSIS IN RESPONDING THE MAGUINDANAO MASSACRE - Abhipraya, Fairuz Arta; Candra, Ilham Agustian; Gauhar, Fasih Raghib (Journal of Terrorism Studies, 2023)
The Association of Southeast Asian Nations (ASEAN) is one of the regional organizations that aims to promote economic and security cooperation among its members in southeast Asia countries. In the dynamics of ASEAN’s journey, the most debated issue is enforcing human rights among ASEAN members. One of the bloodiest tragedies of human rights violations in Southeast Asia has known as the Maguindanao massacre in the Philippines. This research explores more profoundly the responses of the ASEAN on victims’ family requests in the case of the Maguindanao massacre. This research also applies the human rights regime theory to the role of the ASEAN Intergovernmental Commission on Human Rights (AICHR). Through bibliometric analysis by utilizing NVivo 12 plus software for data collection and data visualization, this research found the victim’s family request: further investigation, arrest of perpetrators, public awareness improvement, protection rights, and compensation. Four ASEAN member states, namely Indonesia, the Philippines, Thailand, and Malaysia, have responded to this matter. The ASEAN highlighted five responses: advocacy, lack of mechanism, non-intervention, responsibility transfer, and warn. Eventually, the AICHR has indicated the status of a promotion regime based on its involvement in these issues.